Peningkatan Implementasi Sanitasi Lingkungan melalui Pelatihan bagi Siswa Sekolah Dasar di Bogor - Ima Kusumanti; Hanna Maria Sitindaon; Fiha Nurfatharani; Anisa Istiqomah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Clean and healthy life behavior (PHBS) in schools is an activity to empower students, teachers, and the community to run a healthy lifestyle and create healthy schools. The activity aims to socialize the importance of environmental sanitation in schools and raise awareness about the importance of environmental health in schools, through socialization and implementation training conducted in September 2020 in Bantarjati District, Bogor City, West Java. The activity was followed by students in grade 4 (four) elementary school totaling 35 students with implementation activities consisting of the preparation, core program and evaluation stages, then analyzed qualitatively through field observations and participant understanding interviews. The implementation of sanitation that has been carried out on students is one of the basic sanitation, which is washing hands and sorting waste by type. Minister of Health Regulation No. 3 of 2014 concerning STBM explains that washing hands with soap is the behavior of washing hands using clean running water and soap. Waste in general is divided into two, namely organic and inorganic waste. Both of these wastes have benefits for us, but they also have an impact on the environment. The results of this activity are students knowing the importance of maintaining environmental sanitation and environmental health (hygiene), so that it can be applied in daily life through implementation training (practice). Keyword: health, sorting, washing, garbage, environmental sanitation.